The Mirrlees Approach to Mechanism Design with Renegotiation (with Applications to Hold-up and Risk Sharing) - Segal, Ilya; Whinston, Michael D. (Econometrica, 2002)
The paper studies the implementation problem, first analyzed by Maskin and Moore (1999), in which two agents observe an unverifiable state of nature and may renegotiate inefficient outcomes following play of the mechanism. We develop a first-order approach to characterizing the set of implementable utility mappings in this problem, paralleling Mirrlees's (1971) first-order analysis of standard mechanism design problems. We use this characterization to study optimal contracting in hold-up and risk-sharing models. In particular, we examine when the contracting parties can optimally restrict attention to simple contracts, such as noncontingent contracts and option contracts (where only one agent sends a message).